2018
DOI: 10.1039/c7cp08409a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of polarization and ion conduction mechanisms in hydroxyapatite

Abstract: We report first-principles simulation of polarization mechanisms in hydroxyapatite to explain the underlying mechanism behind the reported ion conductivities and polarization under electrical poling at elevated temperatures. It is found that ion conduction occurs mainly in the column of OH- ions along the c-axis through a combination of the flipping of OH- ions, exchange of proton vacancies between OH- ions, and the hopping of the OH- vacancy. The calculated activation energies are consistent with those found … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
1
11
1
1
Order By: Relevance
“…The hopping energy ( W ) and the hopping range ( R ) show a linear variation with temperature. The obtained W is shown to closely relate to the theoretical studies that predict OH – flipping in the energy range . Finally, a W and R modeling reveals a cubic dependence upon the at.…”
Section: Introductionsupporting
confidence: 73%
“…The hopping energy ( W ) and the hopping range ( R ) show a linear variation with temperature. The obtained W is shown to closely relate to the theoretical studies that predict OH – flipping in the energy range . Finally, a W and R modeling reveals a cubic dependence upon the at.…”
Section: Introductionsupporting
confidence: 73%
“…The values of W as well as R are found to be similar to the present case. Interestingly, Kasamatsu and Sugino pointed out that the polarization mechanisms active within HAP specimens, especially in the activation energy domain of 0.2–0.8 eV, are consistent with the range of hopping energy in the case of ceramics. Tanaka et al reported that in HAP, the dipolar relaxation occurs with an activation energy of 0.6 eV.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Recently, HAP has also drawn attention for industrial purposes. [11][12][13][14][15][16] It is worth mentioning that nanocrystalline HAP particles exhibit superior characterizations for different applications due to enhanced stoichiometry, morphology, and high surface activity and homogeneity. [17][18][19][20] Therefore, preparation of HAP with the most appropriate properties is a pivotal issue that encourages scientists to focus on the synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, having acceptable thermodynamic stability in biofluids makes HAP a prominent candidate for different clinical applications 9,10 . Recently, HAP has also drawn attention for industrial purposes 11–16 . It is worth mentioning that nanocrystalline HAP particles exhibit superior characterizations for different applications due to enhanced stoichiometry, morphology, and high surface activity and homogeneity 17–20 .…”
Section: Introductionmentioning
confidence: 99%